Conformational dynamics of AcrA govern multidrug efflux pump assembly - Hazel, Anthony J. (ACS Infect Dis, 2019)
Multidrug efflux pumps of pathogenic, Gram-negative bacteria comprise an innate resistance mechanism and are key contributors to the emerging global pandemic of antibiotic resistance. Several increasingly detailed cryo-electron microscopy maps have been resolved of an entire efflux pump complex, AcrAB-TolC, resulting in atomistic structural models. Using a recent model, we have carried out nearly 40 μs of molecular dynamics simulations to study one of the key components of the protein complex, AcrA, the membrane fusion protein that connects the inner-membrane-bound AcrB to the outer-membrane-bound TolC. We determined a three-dimensional potential of mean force (PMF) for AcrA, which displays two main conformational basins representing assembly-competent and incompetent states. Corresponding experiments show that stabilizing mutations at an inter-domain interface shift the dynamic equilibrium between these states to the incompetent one, disrupting pump assembly and function and re-sensitizing bacteria to existing antibiotics. Modulation of AcrA dynamics through pharmacological intervention therefore presents a promising route for the development of new antibiotics.